1977
DOI: 10.1111/j.1365-2125.1977.tb00764.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of mental arithmetic in normotensive and hypertensive subjects, and its modification by beta‐adrenergic receptor blockade.

Abstract: I The effects of a 5-min period of sustained mental arithmetic upon blood pressure and heart rate were determined in several groups of healthy subjects and hypertensive patients. 2 The arithmetic produced significant increases in heart rate and blood pressure (both systolic and diastolic) in both normotensive and hypertensive subjects. 3 The blood pressure changes were neither attenuated nor enhanced by the prior administration of ,B-adrenergic receptor blocking drugs (alprenolol, propranolol or metoprolol) on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
15
0

Year Published

1978
1978
1999
1999

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 11 publications
5
15
0
Order By: Relevance
“…To generalize, mental tasks elicit primarily cardiac output (mostly heart rate)-mediated elevations in arterial pressure (Hejl, 1957) as observed in most subjects in this study. Studies of responses to mental tasks during f8-blockade (Nyberg, Graham & Stokes, 1977;Freyschuss, Hjemdahl, Juhlin-Dannfelt & Linde, 1988) suggest that if one mechanism (e.g. heart rate) for elevating arterial pressure during the task is constrained or eliminated, a different mechanism will compensate so that a given increase in arterial pressure is generated.…”
Section: Discussionmentioning
confidence: 99%
“…To generalize, mental tasks elicit primarily cardiac output (mostly heart rate)-mediated elevations in arterial pressure (Hejl, 1957) as observed in most subjects in this study. Studies of responses to mental tasks during f8-blockade (Nyberg, Graham & Stokes, 1977;Freyschuss, Hjemdahl, Juhlin-Dannfelt & Linde, 1988) suggest that if one mechanism (e.g. heart rate) for elevating arterial pressure during the task is constrained or eliminated, a different mechanism will compensate so that a given increase in arterial pressure is generated.…”
Section: Discussionmentioning
confidence: 99%
“…Emotional or mental stress provokes autonomic adjustments, which in turn cause the typical hemodynamic changes characterized by increased heart rate and blood pressure [1][2][3][4]. Although these effects are part of a normal physiological response, mental stress or emotion may also produce myocardial ischemia [5][6][7], decreased left ventricular ejection fraction [7], and ventricular arrhythmia in patients with coronary artery disease [6,[8][9][10].…”
mentioning
confidence: 99%
“…Also the rise in pressure in response to mental arithmetic was reduced by propranolol, 320mg/day (Guazzi et al, 1976). However, Nyberg et al (1977) using lower doses of propranolol, or metoprolol, or alprenolol, found that although the peak pressures were reduced in response to mental arithmetic, the rise from baseline was not.…”
Section: Action On Valsalva 'V Manoeuvre and Blood Pressure Response mentioning
confidence: 93%